Current trends in mini-invasive management of spine metastases. Issue 2 (April 2015) - Guarnieri, Gianluigi; Izzo, Roberto; Muto, Mario
The spine is a frequent localization of primary tumours or metastasis involving posterior arch, pedicles and vertebra body, and often causing unsustainable pain. The management of spinal metastasis remains complex, including medical therapy (corticosteroids, chemotherapy), radiotherapy and surgical treatment, or the recent percutaneous mini-invasive approach. The target of all these treatments is to improve the quality of life of patients affected by this type of lesion. Diagnosis of spinal metastasis and then its treatment should be based on the combination of different elements: clinical evaluation, CT, MRI and nuclear medicine patterns, considering the age of the patient, known primary tumour, location of the lesions, single/multiple lesions, pattern of morphology (border, matrix, expansile character, soft tissue extension), density or signal intensity, oncologic instability and expectancy of life. The percutaneous mini-invasive approach for patients affected by secondary lesions involving the spine has as treatment goal of: (1) pain relief improving the quality of life; (2) stability treatment re-establishing the spinal biomechanics, alterated by bone destruction or deformity, preventing pathological fracture; and (3) an anti-neoplastic effect. The aim of this paper is to provide a comprehensive diagnostic and percutaneous approach to the bone metastatic spine lesions, identifying which metamer should be treated to improve patient quality of life, showing the importance of a multi-disciplinary approach to this problem.